2020
DOI: 10.1111/jcmm.15746
|View full text |Cite
|
Sign up to set email alerts
|

E6 hijacks KDM5C/lnc_000231/miR‐497‐5p/CCNE1 axis to promote cervical cancer progression

Abstract: The prevalence of cervical cancer poses great threat to women's health. 1 Annually, over 500 000 patients were diagnosed with cervical cancer and approximately 300 000 died from this disease. 2-4 Due to the widely use of papanicolaou test for early cervical cancer screening and the advancement of therapeutic methods such as surgery operation, chemical treatment and radiotherapy, the incidence of cervical cancer has been reduced by 40%-50% in recent years. 5-7 However, for those advanced cervical cancer patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 44 publications
(75 reference statements)
1
14
0
Order By: Relevance
“…Malfunctions of lncRNAs play a unique role in oncogenesis and progression. A recent study identified the promotion of lnc_000231 in cervical cancer, which acts by interacting with miR ‐ 497 ‐ 5p 30 . The lncRNA ATB binds to EZH2 and downregulates the expression of DAB2IP, CDH1, LATS2, FOXC1 and CDX1, thus facilitating the progression of ovarian cancer 31 .…”
Section: Discussionmentioning
confidence: 99%
“…Malfunctions of lncRNAs play a unique role in oncogenesis and progression. A recent study identified the promotion of lnc_000231 in cervical cancer, which acts by interacting with miR ‐ 497 ‐ 5p 30 . The lncRNA ATB binds to EZH2 and downregulates the expression of DAB2IP, CDH1, LATS2, FOXC1 and CDX1, thus facilitating the progression of ovarian cancer 31 .…”
Section: Discussionmentioning
confidence: 99%
“…The aberrant expression of miR-497-5p plays an essential role in tumorigenesis. miR-497-5p has been proven to be downregulated in NSCLC, gastric cancer, colorectal cancer, ovarian cancer, renal cell carcinoma, and melanoma [88][89][90][91][92][93][94][95]. Furthermore, in vitro and in vivo studies revealed that miR-497-5p overexpression suppressed HCC cell proliferation, colony formation, and metastasis [96].…”
Section: Discussionmentioning
confidence: 99%
“…Modification on H3K4me3 has shown either promoting or discouraging roles in gene expression. For instance, increased demethylation of H3K4me3 by KDM5C has been reported to inhibit the expression of LINC000231 that was related to the pathogenesis of cervical cancer [ 37 ]. In a study by Lv BB et al, increased methylation of H3K4me3 has been reported to be associated with the activation of the MDM2-p21-E2F1 axis [ 38 ].…”
Section: Discussionmentioning
confidence: 99%